Study of the behaviour of bituminous mixtures resistant to fuel - Freire, A. C. (2010)
Fuel spillage on the wearing courses of road and airport pavements can significantly affect fuel resistant bitumen performance. The use of modified bitumen specifically manufactured to give the asphalt mixture a better resistance to the action of the fuel is an interesting solution for use in areas with specific requirements of that point of view. In order to assess the performance of asphalt resistant fuel a study, sponsored by PETROGAL, was developed in LNEC, in which asphalt mixtures were produced with three types of bitumen - a 35/50 pen grade bitumen penetration, and two modified bitumen – were studied for application in wearing courses. One of the modified bitumens has been specially developed to provide increased resistance to fuel. The study comprised a comparative analysis of the behaviour of different asphalt action by fuel, as well as the evaluation of their performance in fatigue tests and permanent deformation behaviour. This paper presents the results obtained from the study, analyzing the benefits of using fuel resistant bitumen in the performance of asphalt mixtures subject to the action of fuel spillage.